The System of Characters in Kim Seung Ok’s story «Seoul, The Winter of 1964» (Journal of Oriental Studies, 2017)
This article is devoted to the study of system of the characters in themain and famous story «Seoul, The Winter of 1964» by the remarkablewriter of Korea in 1960s Kim Seung Ok. In this story Kim Seung Ok keenlyreveals phsycho-social problems that were existed in capitalist Korean societyduring the 1960s, such as crisis of human relationship, alienationfrom society, hopelessness, uncertainty, confusion and discourtesy by describingand portraying the lives and fates of each character, as well asrelationship between them.